2020
DOI: 10.3390/en13030598
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Post-Peak Short-Term and Creep Behavior of Fractured Sandstone

Abstract: Short-term and creep tests of fractured sandstone with different degrees of damage prepared using pre-peak and post-peak unloading tests on intact sandstone were carried out using a servo-controlled rock mechanics system. Based on our experimental results, the influence of confining pressure and damage on short-term mechanical behavior of fractured sandstone with different degrees of damage was first analyzed. The results show that the peak strength, residual strength, elastic modulus, and secant modulus of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The test data acquisition interval between two adjacent stress level was set to 0.5 s, and the data acquisition interval during each stress level was set to 1 s. In Table 1, the average UCS, peak strain and elastic modulus of sandstone-coal composite samples were 14.14 MPa, 0.00871, and 2.36 GPa, respectively. Generally, the creep tests were carried out by methods of single-stage loading, multi-stage loading, and multistage loading and unloading in previous investigations on the creep characteristics of pure coal or rock samples [37][38][39][40][41][42][43][44][45][46]. In this investigation, the short-term uniaxial creep tests with multi-stage loading were conducted on sandstone-coal composite samples.…”
Section: Creep Strengths Of Composite Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…The test data acquisition interval between two adjacent stress level was set to 0.5 s, and the data acquisition interval during each stress level was set to 1 s. In Table 1, the average UCS, peak strain and elastic modulus of sandstone-coal composite samples were 14.14 MPa, 0.00871, and 2.36 GPa, respectively. Generally, the creep tests were carried out by methods of single-stage loading, multi-stage loading, and multistage loading and unloading in previous investigations on the creep characteristics of pure coal or rock samples [37][38][39][40][41][42][43][44][45][46]. In this investigation, the short-term uniaxial creep tests with multi-stage loading were conducted on sandstone-coal composite samples.…”
Section: Creep Strengths Of Composite Samplesmentioning
confidence: 99%
“…The creep tests on rock or coal samples are very important methods to understand the long-term bearing characteristics and failure mechanisms of coal or rock mass [37][38][39][40][41][42][43][44][45][46], and these investigations mainly focused on pure coal or rock samples. Fatemeh and Mark [37] carried out the creep experiments on clay-and carbonate-rich shale samples with short-term (4 h) and long-term (4 weeks) periods, respectively, the results showed that the shale samples follow the same creep trend through time, regardless of the loading history.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations